Rapid adaptation to a novel pathogen through disease tolerance in a wild songbird - Henschen, Amberleigh E; Vinkler, Michal; Langager, Marissa M; Rowley, Allison A; Dalloul, Rami A; Hawley, Dana M; Adelman, James S (PLoS pathogens, 2023)
Animal hosts can adapt to emerging infectious disease through both disease resistance, which decreases pathogen numbers, and disease tolerance, which limits damage during infection without limiting pathogen replication. Both resistance and tolerance mechanisms can drive pathogen transmission dynamics. However, it is not well understood how quickly host tolerance evolves in response to novel pathogens or what physiological mechanisms underlie this defense. Using natural populations of house finches (Haemorhous mexicanus) across the temporal invasion gradient of a recently emerged bacterial pathogen (Mycoplasma gallisepticum), we find rapid evolution of tolerance (<25 years). In particular, populations with a longer history of MG endemism have less pathology but similar pathogen loads compared with populations with a shorter history of MG endemism. Further, gene expression data reveal that more-targeted immune responses early in infection are associated with tolerance. These results suggest an important role for tolerance in host adaptation to emerging infectious diseases, a phenomenon with broad implications for pathogen spread and evolution.
Keywords: objevující se infekční nemoci; imunologická tolerance; nemoci ptáků; Mycoplasma gallisepticum; Bird Diseases; pěnkavovití; Animals; Finches; zvířata; Immune Tolerance; Communicable Diseases, Emerging